Implementation of the Prophet Muhammad's Educational Method According to the Hadith in Ibn Kathir's Interpretation in Early Childhood Education at TAAM Mandiri Cikampek - Eva Hudaebah; Purnianti , Purnianti; Dita Anggraini; Ani Fatria Handayani; Sumiati, Sumiati (STIT Attaqwa, 2025)
Early childhood education is the primary foundation for developing children's character and morals. In Islam, the Prophet Muhammad is the primary role model for implementing educational methods that are humanistic, holistic, and in accordance with the natural development of children. This article aims to examine the Prophet Muhammad's educational methods according to the hadith described in Ibn Kathir's Tafsir and analyze their application in early childhood education at TAAM Mandiri Cikampek. This research used a qualitative approach with a field study. Data collection techniques included observation, interviews with educators, and documentation of learning activities. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the Prophet Muhammad's educational methods, as derived from the hadith in Ibn Kathir's Tafsir, include exemplary behavior (uswah hasanah), habituation, advice (mau'izhah), dialogue, and education based on compassion and gentleness. These methods are relevant to the characteristics of early childhood and align with the principles of child development. The application of the Prophet Muhammad's educational methods at TAAM Mandiri Cikampek is evident in activities that foster worship, instill noble moral values, use polite language, teachers' role models in daily behavior, and an educational approach that emphasizes compassion without violence. The implementation of these methods has a positive impact on children's moral, socio-emotional, and spiritual development. The conclusion of this study indicates that the Prophet Muhammad's educational methods, according to the hadith in Tafsir Ibn Kathir, are highly relevant and applicable for implementation in early childhood education institutions. Therefore, integrating the Prophet Muhammad's educational methods into learning practices at TAAM can serve as an effective Islamic educational model for shaping children's character from an early age.